Pengaruh Modal Kerja, Motivasi, dan Promosi terhadap Pendapatan dengan Lama Usaha sebagai Variabel Moderasi: Studi Kasus UMKM Dodol Pasar Bengkel Serdang Berdagai - Thori , Mhd (Masyarakat Ekonomi Syariah Bogor, 2024)
Increasing income from a business activity that has been carried out within a certain period is very important for every entrepreneur or company. One of the goals of establishing a business or company is to increase income. By increasing income, the company or business can be said to experience positive development. Revenue is every additional asset or reduction in liabilities that arises from the company's business, whether it is the delivery of services or the sale of goods. One of the MSMEs in the culinary sector in Indonesia which is quite well known is in Sumatra, more precisely in the Serdang Bedagai area, which is known as Dodol Pasar Bengkel.